2018
DOI: 10.5851/kosfa.2018.e49
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium Powder Mixtures and Binding Ingredients as Substitutes for Synthetic Phosphate on the Quality Properties of Ground Pork Products

Abstract: This study aimed to investigate the combined effect of using natural calcium mixtures and various binding ingredients as replacers for synthetic phosphate in ground pork products. We performed seven treatments: control (0.3% phosphate blend), treatment 1 (0.5% natural calcium mixtures [NCM, which comprised 0.2% oyster shell calcium and 0.3% egg shell calcium powder] and 0.25% egg white powder), treatment 2 (0.5% NCM and 0.25% whey protein concentrate), treatment 3 (0.5% NCM and 0.25% concentrated soybean prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…The CIE b* values of 60AL and 80AL treatments were lower (p<0.05) than those of control (+) and control (–); however, 100AL treatment had a CIE b* value similar (p>0.05) to that of both the controls. This result was consistent with that of Cho and Jeong (2018), who found that CIE b* values of products treated with oyster shell calcium, egg shell calcium, and whey protein concentrate were not different from that of the control treated with phosphate.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The CIE b* values of 60AL and 80AL treatments were lower (p<0.05) than those of control (+) and control (–); however, 100AL treatment had a CIE b* value similar (p>0.05) to that of both the controls. This result was consistent with that of Cho and Jeong (2018), who found that CIE b* values of products treated with oyster shell calcium, egg shell calcium, and whey protein concentrate were not different from that of the control treated with phosphate.…”
Section: Resultssupporting
confidence: 92%
“…The pH values increased (p<0.05) with the level of added phosphate replacer. These results may be due to the addition of egg shell calcium and oyster shell calcium powder, as reported in previous studies (Cho et al, 2017; Cho and Jeong, 2018). However, no differences (p>0.05) in the moisture content were observed between the controls and the treatments (Table 2).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Konjac is well known to strengthen the water binding ability of meat products [14]. Thus, it is well known that hydrocolloids enhance water retention and texture in meat products [15,16]. However, the synergistic effect of combining hydrocolloids with meat jelly was not studied.…”
Section: Introductionmentioning
confidence: 99%